Effect of air factor in gasification of empty fruit bunch in fluidized bed [electronic resource] - 284496 Muhammad Nasyiruddin Indrawarman (2009)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2009